2003
DOI: 10.1038/sj.ejcn.1601758
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomised trial to determine the efficacy of a low glycaemic index diet given in addition to healthy eating and weight loss advice in patients with coronary heart disease

Abstract: Objective: Recent epidemiological and prospective trial evidence suggests that consumption of a low glycaemic index (LGI) diet will reduce coronary risk. We hypothesise that introduction of an LGI diet will improve the metabolic profile of patients who have undergone coronary artery bypass grafting. Design: We conducted a randomised parallel group trial comparing a control group (n ¼ 29, age 61.879 y), who received currently advocated healthy eating dietary advice only, to an intervention group, who received h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 21 publications
1
26
0
Order By: Relevance
“…Of these reports, 226 were excluded based on other criteria, leaving 41 trials (39 reports) that satisfied the inclusion criteria but did not meet the exclusion criteria, of which 11 trials (ten reports) investigated pulses alone, 19 trials (19 reports) investigated pulses in a low-GI dietary intervention, and 11 trials (ten reports) investigated pulses in a high-fibre dietary intervention. Tables 1, 2, and 3 show the characteristics of the 41 randomised controlled experimental trials included in each of the three meta-analyses: pulses alone [45][46][47][48][49][50][51][52][53][54], pulses in low-GI diets [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] and pulses in highfibre diets [55][56][57][58][59][60][61][62][63][64]. The 11 trials (ten reports) investigating pulses alone (Table 1) were predominantly crossover in design (seven trials, five of which had a washout period), studied a total of 253 participants (type 2 diabetes, n=21; normoglycaemia and/or hypercholesterolaemia, n=232) and had a mean sample size of 23.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these reports, 226 were excluded based on other criteria, leaving 41 trials (39 reports) that satisfied the inclusion criteria but did not meet the exclusion criteria, of which 11 trials (ten reports) investigated pulses alone, 19 trials (19 reports) investigated pulses in a low-GI dietary intervention, and 11 trials (ten reports) investigated pulses in a high-fibre dietary intervention. Tables 1, 2, and 3 show the characteristics of the 41 randomised controlled experimental trials included in each of the three meta-analyses: pulses alone [45][46][47][48][49][50][51][52][53][54], pulses in low-GI diets [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] and pulses in highfibre diets [55][56][57][58][59][60][61][62][63][64]. The 11 trials (ten reports) investigating pulses alone (Table 1) were predominantly crossover in design (seven trials, five of which had a washout period), studied a total of 253 participants (type 2 diabetes, n=21; normoglycaemia and/or hypercholesterolaemia, n=232) and had a mean sample size of 23.…”
Section: Methodsmentioning
confidence: 99%
“…In early studies, pulses were shown to result in exceptionally low glycaemic responses when fed to healthy volunteers [11], and in later experiments were demonstrated to possess a carbohydrate component that was more slowly digested than that of other foods such as cereals [12]. This property of slower absorption, which is common to α-glucosidase inhibitors, makes pulses an important means of lowering the GI of the diet, a characteristic that has been exploited extensively in studies of low-GI diets [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31], and would therefore be predicted to benefit glycaemic control and, by analogy with acarbose, CHD risk [8]. Based on limited clinical experimental evidence, the European (EASD) [32], Canadian (CDA) [33], and American (ADA) [34] diabetes associations recommend the consumption of dietary pulses as a means of optimising diabetes control through lowering the GI and increasing the dietary fibre content of the diet.…”
Section: Introductionmentioning
confidence: 99%
“…GI) more often shows a significant association with disease risk (diabetes, CVD, cancer) than does the CHO content or GL of the diet. Very recently, several other papers and reviews addressed the impact of GI and GL on health aspects (Tavani et al 2003;Frost et al 2004;Kelly et al 2004;Opperman et al 2004). No benefits occurred in the Frost study, but according to the authors it cannot be excluded that potential effects may have been concealed due to drug therapy.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the GI values of HCJ were determined in accordance with the procedures that have been well-established in the GI literature [10,11,12]. Blood samples were taken from the finger using an automatic lancet (Safe-T-Pro, Germany) 15, 30, 45, 60, 90, and 120 min into the application, and each time the amount of glucose was determined by a glucometer.…”
Section: Determination Of Glycemic Indexmentioning
confidence: 99%
“…The GI was calculated as the percent of glycemic area determined after the consumption of HCJ to the glycemic area produced by the glucose that was chosen as the standard [13]. The commonly-used GI classification system categorizes food into 3 groups, as low (<55), medium (55-69) or high GI (>70) [11]. The HCJ samples in this study were classified according to the GI results.…”
Section: Determination Of Glycemic Indexmentioning
confidence: 99%